Pengaruh COVID-19 Related HRM Strategies Terhadap Job Performance Dengan Dimediasi Oleh Work Motivation Dan Innovation Climate (Jurnal Ekonomi : Journal of Economic, 2023)
The purpose of this study is to identify how HRM strategies related to COVID-19 affect performance and innovation climate. This study uses purposive sampling technique which is part of non-probability sampling and data analysis techniques using validity and reliability tests, hypothesis testing, multiple linear regression analysis, and hypothesis testing processed with SPSS version 22.0 and Amos version 22.0 software. Data collection in this study was on a sample of 139 employees at service companies in Jakarta, Indonesia. In this study, the authors tested the Effect of HRM Strategies Related to COVID-19 on Work Performance Mediated by Work Motivation and Innovation Climate. Based on the results of the analysis and discussion, it can be interpreted that Work Motivation and Innovation Climate have a positive effect on Work Achievement. The implications of the results of the research conducted to regulate COVID-19 Related HRM Strategies at service companies in Jakarta, it is important to know which strategy changes are suitable to be adjusted during a pandemic because every change in strategy greatly affects employees, especially Job Performance, it is necessary to pay attention to employee Work Motivation & Innovation Climate. To improve Job Performance can pay attention to and improve Work Motivation, Innovation Climate. Job Performance is the result of work or output produced (output) in accordance with the duties and responsibilities in the organization, which involves standards, job criteria, job quality, and job quantity.